PENGARUH AUDIT KINERJA DAN SISTEM PENGENDALIAN INTERN TERHADAP GOOD GOVERNMENT GOVERNANCE (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Siak) - Muhammad Irfan; Nur Azlina; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This researchis to determine the effect of the performance audit and internal control system of good government governance. Population in this research are civil servants in 28 work units siak district. While respondents consisted of a head of department, chief financial subdivision planning and financial planning staff totaling 68 people. The sampling method used in this research is purposive sampling, while data processing method used in this research is multiple regression analysis using SPSS software for data processing 21. The conclusion are that the performance audit and internal control system significant effect on good government governance. Furthermore the determination test which adjusted R2 of 0,754 or 75,4% indicates that the performance audit and internal control system affecting the good government governance. While the remaining 24,6% is influenced by other variables.Keyword : audit performance, internal control system, good government governance